Optical Design of a Solar Simulator With Large Irradiation Surface and High Irradiation Uniformity - Shi Liu; Gaofei Sun; Guoyu Zhang; Siwen Chen; Jiali Chen; Jierui Zhang (IEEE Photonics Journal, 2022)
Aiming at the problem of low irradiation uniformity in existing solar simulators with large irradiation surface, a new optical design method of off-axis TMA (three-mirror anastigmat) solar simulators with large irradiation surface high uniformity was proposed. Three groups of short arc xenon lamps and non-coaxial ellipsoid mirror are used as composite light sources, the causes of stray light in optical integrator are clarified, and the optimization design method of integrator based on anti-crosstalk diaphragm is proposed. The light propagation matrix model of the optical system of the solar simulator is established to effectively suppress stray light in the integrator, and the influence of the aberration of the collimating system on the irradiation uniformity was analyzed. A optical system of object side telecentric off-axis TMA was designed to achieve high uniform illumination with large irradiation area. The results show that in the Φ500 mm irradiation surface, the irradiance of the system is better than 1S0 (1367 w/m2), up to 1656 w/m2, irradiation uniformity is 98.29%, this research can provide accurate and reliable solar radiation for space environment experiment of satellite load and make up for the limitation of low irradiation uniformity of traditional solar simulators with large irradiation surface.